From application descriptions to hardware in seconds a logic-based approach to bridging the gap. - Benkrid, K.
This paper presents a high-level hardware description environment developed at Queen's University, Belfast, U.K., which aims to bridge the gap between application design and hardware description. The environment, called application-to-hardware (A2H), allows for efficient compilation of high-level application descriptions to field programmable gate array (FPGA) hardware in the form of EDIF netlist in seconds. A key concept in bridging the gap while retaining the hardware efficiency, is that of hardware skeletons. A hardware skeleton is a parameterized description of a task-specific architecture, to which the user can supply not only value parameters but also functions or even other skeletons. A skeleton contains built-in rules, which capture optimizations specific to the target hardware at the implementation phase. The rule-based logic programming language Prolog has been chosen as the base notation for the A2H environment. This paper includes descriptions of hardware skeletons abstractions in the particular context of image processing applications. The current implementation of our system targets Xilinx XC4000 and Virtex series FPGAs.
Keywords: Prolog; Xilinx FPGA; Application design; Application-to-hardware.; Built-in rules; Electronic design automation; Hardware skeletons; High-level hardware description environment; Image processing; Logic programming; Reconfigurable systems; Task-specific architecture; Video processing